Incidence and Predictors of Venous Thromboembolism After Debulking Surgery for Epithelial Ovarian Cancer - Mokri, Bahareh (Int J Gynecol Cancer, 2013)
OBJECTIVE: The aim of this study was to determine the incidence and the risk factors of venous thromboembolism (VTE) within 30 days after primary surgery for epithelial ovarian cancer (EOC). METHODS: In a historical cohort study, we estimated the postoperative 30-day cumulative incidence of VTE among consecutive Mayo Clinic patients undergoing primary cytoreduction for EOC between January 2, 2003, and December 29, 2008. We tested perioperative patient characteristics and process-of-care variables (defined by the National Surgical Quality Improvement Program, >130 variables) as potential predictors of postoperative VTE using the Cox proportional hazards modeling. RESULTS: Among 569 cases of primary EOC cytoreduction and/or staging and no recent VTE, 35 developed symptomatic VTE within 30 days after surgery (cumulative incidence = 6.5%; 95% confidence interval, 4.4%–8.6%). Within the cohort, 95 (16.7%) received graduated compression stockings (GCSs), 367 (64.5%) had sequential compression devices + GCSs, and 69 (12.1%) had sequential compression devices + GCSs + postoperative heparin, with VTE rates of 1.1%, 7.4%, and 5.8%, respectively (P = 0.07, χ(2) test). The remaining 38 (6.7%) received various other chemical and mechanical prophylaxis regimens. In the multivariate analysis, current or past tobacco smoking, longer hospital stay, and a remote history of VTE significantly increased the risk for postoperative VTE. CONCLUSIONS: Venous thromboembolism is a substantial postoperative complication among women with EOC, and the high cumulative rate of VTE within 30 days after primary surgery suggests that a more aggressive strategy is needed for VTE prevention. In addition, because longer hospital stay is independently associated with a higher risk for VTE, methods to decrease length of stay and minimize factors that contribute to prolonged hospitalization are warranted.